Intra-articular injections - current indications and contraindications - Mateusz Szubstarski; Przemysław Sekuła; Łukasz Głodek; Marta Tarczyńska; Krzysztof Gawęda; Rafał Mazur (Kazimierz Wielki University, 2017)
Therapeutic intra-articular injections are becoming an increasingly popular treatment modality for osteoarthritis, in particular in its initial stage. The available literature provides varied reports on the efficacy of drugs being administered directly into the joint cavity. This results from inconsistent research methods and assessment criteria. There is considerable controversy as to the best therapeutic approach in everyday clinical practice. The aim of this paper was to present synthetically information and research results concerning the use of selected therapeutic agents in intra-articular injection treatment. The collected data is supposed to facilitate adjusting treatment strategies to patients' individual needs.